The Effect of the Double Loop Problem Solving Model on Problem Solving Ability and Critical Thinking Skills - Ghina Tsania Arsya; Wahidin Wahidin; Mufti Ali (Universitas Islam Negeri Walisongo Semarang, 2023)
Problem solving abilities and critical thinking skills are 21st century skills that need to be developed with efforts to apply innovative learning models, namely double loop problem solving model. This study aims to determine the effect of the double loop problem solving model on students' problem solving abilities and critical thinking skills. The research method uses a quasi experiment with a nonequivalent control group research design. Data collection techniques using pretest and posttest. The data is processed by conducting analysis prerequisite tests in the form of a normality test, homogeneity test while the hypothesis test uses the one way ANOVA and post hoc follow-up tests. Based on the results of the research, it can be concluded that there is an influence of the double loop problem solving learning model on the problem solving abilities and critical thinking skills of students on biodiversity material in class X MIPA SMAN 4 Tasikmalaya in the 2022/2023 academic year